Evaluasi Program Pelayanan Kesehatan Lanjut Usia di Wilayah Kerja Puskesmas Pusako Kabupaten Siak - Neni Suryani; Budi Hartono; Hendri Hendri (LPPM Hang Tuah Pekanbaru, 2023)
One of the successful efforts to improve the social welfare of the elderly is to improve the standard of living and Life Expectancy (UHH). In Siak Regency, the coverage of the elderly who have just received health services at community health centers in 2020 is around 3.7% (100% target). It aims to identify problems, prioritize problems, determine alternative solutions to problems, and create an Intervention Plan (Plan of Action) in accordance with alternative problem-solving related to the Evaluation of Elderly Programs at the Pusako Community Health Center. This research used qualitative methods, using document tracing data sources, direct observations, and field observations in the elderly unit. The informants are the Head of the Center for Public Health, the Head of Administration, the Elderly Program Holder, and employees in the elderly unit. It was found that there was no evaluation of the elderly program. So that the recording and reporting carried out are not in accordance with the achievements. The recommendation is that it is expected that the Head of the Center for Public Health needs to audit the documents and evaluate the recording and reporting of the elderly program in a comprehensive manner.